The effect of internal auditing on the financial performance of an organization - Nyirambonigaba Phionah (UCU, 2024)
ABSTRACT This study examined how internal auditing affects financial performance of an organization, concentrating on Stanbic Bank Garden City Branch. The main objective was to examine the effect of internal auditing on the financial performance of Stanbic Bank Garden city branch in Kampala. This study was conducted with three objectives in mind: to find out the effect of control activities on financial performance of Stanbic bank Garden City branch, to find out the effect of monitoring activities on financial performance of Stanbic Bank Garden City branch, to find out the effect of audit risk management on the financial performance of Stanbic bank Garden City branch. Through qualitative research method, data was collected from bank staff and management through questionnaires. The findings suggest that effective internal auditing significantly enhances financial performance by identifying inefficiencies, mitigating risks, and promoting better decision making. Moreover, the study highlights the importance of continuous audit process and the role of internal auditors in safeguarding the financial integrity of an organization. The research concludes that robust internal auditing practices are essential for sustaining and improving financial performance in banking sector. Recommendations include, strengthening the internal audit function through regular training, adoption of advanced audit technologies, and ensuring audit independence to enhance the reliability and effectiveness of the audit process.